New Netherland and the Dutch origins of American religious liberty - Haefeli, Evan, 1969- (Early American studies., 2012)
Especially examines the experiences of Jews, Lutherans, Quakers, Baptists, and members of other groups not part of the official Dutch Reformed Church in New Netherland.